Manggaraian People's Perspective on Migration: A Study of Popular Manggaraian Songs' Lyrics - Ans Prawati Yuliantari; Yohanes S. Lon; Fransiska Widyawati (MOZAIK HUMANIORA, 2020)
Migration is one of important issues in the Manggaraians' life. Their migration from Manggarai to various regions in Indonesia has made subtantial impacts on Manggaraian society. Over a long period of time, they have transformed from an agrarian society into an industrial society. This socioeconomic shift has become one of recurrent themes in Manggaraian popular songs. Two of the songs featuring this theme are “Lelak Loce Renda” written by Felix Edon and “Hemong Beo” written by Yasintus S.A. Jaar. Two questions that the present study intends to answer are, what factors encourage Manggaraian people to migrate out of their home region according to the lyrics of the abovementioned two songs? and how do they perceive migration as part of their socioculturalral realities? The answers to these questions are developed using a sociocultural perspective based on a theoretical concept posited by Everett E.Lee named pull and push factors. The study has led to the conclusion that the factors that has motivated the Manggaraians to migrate out of their home region thus far can be grouped into "push" factors and "pull" factors. The greatest push factor is found in a Manggaraian cultural value called goet-goet because of which they see migrating for better future is a respectable decision. The greatest pull factor is the expectation that the places to which they want to migrate offer more economic opportunities than those available in their hometown or home villages.